Study on the dc flashover performance of standard suspension insulator with ring‐shaped non‐uniform pollution. Issue 2 (1st June 2018) - Zhang, Zhijin; Zhao, Jiayao; Zhang, Dongdong; Jiang, Xingliang; Li, Yongfu; Wu, Bin; Wu, Jian
Abstract : Under dc electric field, pollution may be more easily deposited around insulator string caps and pins, distributing non‐uniformly on its inner and outer parts, and presenting ring‐like shape. dc Flashover tests of 7‐unit XHP‐160 insulator string were carried out. During the tests, the ring‐shaped non‐uniform pollution was simulated using solid‐layer method by changing the ratio I/O of inner‐to‐outer surface salt deposit density (SDD) and radius ( r ) of the heavily polluted area (the inner part). On the basis of the test data, the effects of ring‐shaped non‐uniform pollution on dc flashover characteristics were studied. Then, the relative variation trend of flashover voltage, surface pollution layer resistance, and leakage current were discussed. Research results show that the ratio I/O affects the dc flashover performance of the insulator string. The flashover voltage increases with the increase of I/O . With the increase of the radius r, the flashover voltage will increase at first and then decrease. Under ring‐shaped non‐uniform pollution, surface pollution layer resistance of insulator will increase, which results in lower leakage current and higher flashover voltage. The results will be of certain value in providing references for outdoor insulation selection.